Population changes in the vicinity of Wrocław in 1988-2021 as an expression of the formation of the urban functional area - Potocki, Jacek (Zmiany zaludnienia okolic Wrocławia w latach 1988-2021 jako wyraz kształtowania miejskiego obszaru funkcjonalnego, 2025)
Aim: The purpose of this article is to diagnose the process of formation of the Wroclaw urban functional area, in particular the suburban zone, which is the strict hinterland of the metropolitan centre, and to determine the extent of this zone. Methodology: The research used cartographic analysis, relying on population data for Wroclaw and the neighbouring areas from the national census conducted in 1988, 2002, 2011 and 2021. Results: The research showed that the contemporary suburban zone of Wroclaw, designated as an area covered by suburbanization processes, emerged only after 1988, with its extent not coinciding with the urban functional area designated in official strategic and planning documents. Implications and recommendations: The results of the study suggest the desirability of delimiting the Wrocław Urban Area covering Wrocław and the suburban zone strictly adjacent to the city, which requires a special approach in development policy, different from that for the other parts of the broad Wrocław Functional Area. It also seems justified to deepen the research in order to delimit the Wrocław suburban zone more precisely and to consider changes in the administrative division. Originality/value: All analyses to date aimed at delimiting the urban functional area of Wrocław (as well as other metropolitan centres in Poland) have been based on aggregate statistical data aggregated by municipality. This article presents an attempt to delimit the suburban zone on the basis of more detailed data concerning individual localities. As a result, the zone thus delimited is territorially smaller but internally more homogeneous.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 148-160
Keywords: Wroclaw; functional urban area; suburbanisation; regional and local development; Wrocław; miejski obszar funkcjonalny; suburbanizacja; rozwój regionalny i lokalny